The relationship between vLTP and vVO2max during an incremental test to exhaustion in professional endurance runners - Gaeini, A. A.; Rahnama, N.; Kordi, M. R.; Khaledi, N. (Sport Sciences for Health, 2008)
The minimal running velocity at which maximal oxygen uptake (VO2max) is elicited during an incremental test to exhaustion has been used to prescribe training for competitive middle- and long-distance runners. The purpose of this study was to determine the relationship between velocity at lactate turnpoint (vLTP) and vVO2max in long-distance runners. For this purpose 11 highly trained endurance runners were selected randomly from the national team. The average age, height and mass of the subjects were 24.36±1.1 years, 1.73±0.02 m and 63.25±21 kg respectively. The first test was used to determine vVO2max and VO2max (a continuous run to exhaustion with the start velocity at 10 km/h and the velocity increased 1 km/h per minute). The second test was used to determine vLTP (start velocity was 10 km/h and velocity increased 1 km/h for 4 min to reach lactate concentration over 5 mmol/l). The average VO2max and vVO2max of subjects were 58.54±2.8 ml/kg/min and 19±0.29 km/h respectively. Pearson`s correlation coefficient and SPSS 12 software were used for analysing data. There was a positive moderate correlation between vLTP and vVO2max (p=0.037, r=0.63). This study may indicate that, the more the athlete is capable of delaying the accumulation of his/her lactate, and the higher the velocity at which the accumulation takes place, the higher vVO2max he/she can have. On the other hand, coaches can design training programmes at vVO2max intensity to promote a higher vLTP.